2020
DOI: 10.1080/13696998.2020.1762620
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden in patients with ALK + non-small cell lung cancer, with or without brain metastases, receiving second-line anaplastic lymphoma kinase (ALK) inhibitors

Abstract: Jahanzeb (2020) Economic burden in patients with ALK + non-small cell lung cancer, with or without brain metastases, receiving second-line anaplastic lymphoma kinase (ALK) inhibitors,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 35 publications
(52 reference statements)
3
17
0
Order By: Relevance
“…In our study, PPPM costs in patients with BM comprised more inpatient costs than outpatient costs. This is consistent with previous studies that showed more PPPM costs in inpatient settings than in outpatient settings in patients with BM [ 19 , 20 ]. Moreover, as medications and radiation therapy have been suggested as the main cost drivers in patients with BM [ 19 ], drug costs comprised the greatest part of the total costs, followed by radiology/radiotherapy in our study.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In our study, PPPM costs in patients with BM comprised more inpatient costs than outpatient costs. This is consistent with previous studies that showed more PPPM costs in inpatient settings than in outpatient settings in patients with BM [ 19 , 20 ]. Moreover, as medications and radiation therapy have been suggested as the main cost drivers in patients with BM [ 19 ], drug costs comprised the greatest part of the total costs, followed by radiology/radiotherapy in our study.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous studies that showed more PPPM costs in inpatient settings than in outpatient settings in patients with BM [ 19 , 20 ]. Moreover, as medications and radiation therapy have been suggested as the main cost drivers in patients with BM [ 19 ], drug costs comprised the greatest part of the total costs, followed by radiology/radiotherapy in our study. These greatest cost components were incurred in both inpatient and outpatient settings, with drug costs incurred mostly in outpatient settings and radiology/radiotherapy costs incurred mostly in inpatient settings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations